Advanced wastewater treatment method based on adsorbent
The method addresses the inefficiencies of current fly ash treatment by using a carbon dioxide pre-treatment with iron-sulfur magnetic biochar and electro-dialysis to remove chlorides and heavy metals from fly ash leachate, ensuring environmental compliance and resource efficiency.
Patent Information
- Application Number
- CN202510811911.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-07-15
- Estimated Expiration
- 2045-06-18
AI Technical Summary
The prior art has the problem of high chlorine and heavy metal content when dealing with waste incineration fly ash water washing liquid, which leads to water resource pollution and health hazards. The traditional pretreatment method is costly and inefficient.
Using iron-sulfur magnetic mesoporous biochar and bipolar membrane electrodialysis technology, calcium ions are removed through pretreatment, heavy metals are adsorbed by loaded iron-sulfur magnetic mesoporous biochar, and chlorine in the washing solution is separated by electrodialysis, and ion exchange membrane with good chlorine resistance is prepared to achieve efficient removal.
Effectively reduce the heavy metal and chlorine content in the water washing liquid, meet sewage discharge standards, realize water resource conservation and harmless treatment, and reduce treatment costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution control and treatment, and specifically to a method for deeply treating wastewater based on an adsorbent. Background Art
[0002] Municipal solid waste incineration fly ash is a by-product in the process of municipal solid waste incineration treatment. In municipal solid waste incineration fly ash, in addition to 20%-30% soluble chlorides, there are also harmful substances such as heavy metal-based dioxins. Therefore, municipal solid waste incineration fly ash is identified as hazardous waste. At present, the treatment methods for municipal solid waste incineration fly ash include solidification and landfill, co-processing in cement kilns, low-temperature pyrolysis, and high-temperature sintering. However, when these methods are used to treat municipal solid waste incineration fly ash, the municipal solid waste incineration fly ash needs to be pretreated to remove the chlorine and heavy metals therein. The commonly used pretreatment methods include pickling, alkali washing, and water washing. Pickling can easily dissolve about 90% of the substances in the fly ash, and alkali washing can solidify the heavy metals in the fly ash and retain almost 100% of the calcium in the fly ash. However, the pickling and alkali washing treatment methods require a large amount of acid and alkali chemical reagents, and at the same time increase the cost of treating acid and alkali waste liquid, and the economic value of municipal solid waste incineration fly ash is relatively low. Therefore, for cost considerations, at present, the most commonly used fly ash pretreatment method in the industry is water washing.
[0003] In the water washing solution obtained by treating municipal solid waste incineration fly ash by water washing, there are a large amount of soluble chlorides and trace amounts of harmful components such as heavy metals. If directly discharged, the chlorides in the water washing solution will cause soil alkalization, resulting in the death of farmland plants, and the heavy metals in the water washing solution will accumulate in animals and plants, endangering the health of residents. Therefore, it is necessary to treat the fly ash water washing solution to remove the chlorine and heavy metals in the water washing solution so that it meets the sewage discharge standard, thereby realizing the needs of saving water resources and harmless treatment of the water washing solution. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for deeply treating wastewater based on an adsorbent, which removes heavy metals through the adsorbent and separates chlorine in the water washing solution by electrodialysis, solves the problem of high chlorine and heavy metal contents in the water washing solution, enables the water washing solution to meet the sewage discharge standard, and realizes the needs of saving water resources and harmless treatment of the water washing solution.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for deeply treating wastewater based on an adsorbent, specifically as follows: Step 1: Introduce a mixed gas of carbon dioxide and air into the fly ash water washing solution to perform decalcification pretreatment on the fly ash water washing solution to obtain a decalcified water washing solution; Step 2: Add the iron-sulfur magnetic mesoporous biochar and persulfate into the decalcified washing solution, and stir at a speed of 150 - 200 rpm for 90 - 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, and filter to obtain the secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane to obtain the advanced treated wastewater.
[0006] As a limitation of the present invention, in Step 1, the volume ratio of carbon dioxide to air is 1:(5 - 10), and the flow rate of the mixed gas is (1 - 5) mL / min; during the aeration process, always pay attention to the pH of the washing solution, and stop aeration after the pH of the washing solution becomes neutral.
[0007] As a limitation of the present invention, the preparation method of the iron-sulfur magnetic mesoporous biochar is as follows: Dry the straw at 80 - 90 °C, crush it to remove impurities, and grind it to obtain straw powder with a particle size of 100 - 150 μm. Mix the straw powder, potassium bicarbonate, and potassium chloride, and ball mill for 15 - 20 min to make them evenly mixed. Under nitrogen as the protective gas, heat it to 850 - 900 °C at a heating rate of 5 °C / min and hold for 2 - 3 h. After the holding is completed, cool it to room temperature in a closed manner. Crush the obtained solid, wash it with deionized water, and dry it at 80 - 90 °C to obtain mesoporous biochar; Add the mesoporous biochar into deionized water, ultrasonically disperse it for 15 - 20 min, then add ferric chloride and ferrous sulfate, stir evenly to fully dissolve, adjust the pH to 9 - 10 with sodium hydroxide to obtain a biochar suspension. Subsequently, react the biochar suspension in a water bath at 80 - 90 °C for 0.5 - 1 h. During the reaction process, continuously introduce nitrogen into the suspension. After the reaction is completed, separate it with an external magnetic field. Wash the separated product with absolute ethanol and deionized water, and dry it at 80 - 90 °C to obtain magnetic mesoporous biochar; Add ferric nitrate into deionized water, stir evenly, and slowly add thiourea after fully dissolving. Ultrasonically disperse it for 10 - 15 min to form a dispersion. Subsequently, evaporate the dispersion to dryness at 80 - 90 °C. Mix the solid obtained after evaporation with the magnetic mesoporous biochar, and under closed conditions, heat it to 850 - 900 °C at a heating rate of 5 °C / min and hold for 2 - 3 h. After the holding is completed, cool it to room temperature in a closed manner. Crush the product and wash it with 0.1 mol / L hydrochloric acid and deionized water, and dry it at 80 - 90 °C to obtain the iron-sulfur magnetic mesoporous biochar.
[0008] As a limitation of the present invention, the mass ratio of straw powder, potassium bicarbonate, and potassium chloride is (2 - 4):(2 - 4):(8 - 12); the mass ratio of mesoporous biochar, ferric chloride, and ferrous sulfate is (1 - 3):(1 - 3):(0.5 - 1.5); the mass ratio of ferric nitrate, thiourea, and magnetic mesoporous biochar is (0.1 - 0.3):(0.35 - 0.45):(8 - 12).
[0009] As a limitation of the present invention, in step 2, the dosage of the iron-sulfur magnetic mesoporous biochar is 1 - 2% of the mass fraction of the decalcified washing solution; the persulfate is one or a mixture of ammonium persulfate, potassium persulfate, and sodium persulfate, and the dosage is 0.5 - 1% of the mass fraction of the decalcified washing solution.
[0010] As a limitation of the present invention, the bipolar membrane includes a sulfonic acid-phosphoric acid zirconium hybrid cation exchange membrane with a thickness of 0.08 - 0.12 mm, a quaternized nanocellulose hybrid anion exchange membrane with a thickness of 0.08 - 0.12 mm, and a loaded iron catalytic intermediate layer in between, with a thickness of 30 - 50 nm.
[0011] As a limitation of the present invention, the preparation method of the phosphoric acid zirconium hybrid cation exchange membrane is as follows: Add zirconium oxychloride and polyvinylidene fluoride to a mixed solution of N,N-dimethylacetamide and methanol, ultrasonically disperse for 20 - 30 min, and then stand for defoaming for 1 - 2 h to obtain a cation exchange membrane casting solution. Spin-coat the cation exchange membrane casting solution to form a film, and then heat and cure at 60 - 70 °C for 2 - 3 h. After curing is completed, cool to room temperature to obtain a zirconium oxychloride hybrid cation exchange membrane; Immerse the zirconium oxychloride hybrid cation exchange membrane in phosphoric acid solution, heat and react at 110 - 120 °C for 1 - 2 h. After the reaction is completed, cool to room temperature, wash with hydrochloric acid and deionized water, and dry to obtain a phosphoric acid zirconium hybrid cation exchange membrane; Adjust the pH of the Tris buffer solution to 7 - 8 with hydrochloric acid, add sodium polystyrene sulfonate, stir evenly and dissolve completely to obtain a sodium polystyrene sulfonate solution. Under an argon atmosphere, treat the phosphoric acid zirconium hybrid exchange membrane with plasma, control the plasma discharge current to be 4.0 - 5.0 A, and the treatment time to be 5 - 10 min. After the treatment is completed, quickly immerse it in the sodium polystyrene sulfonate solution and soak for 1.5 - 2 h. After soaking is completed, take it out, wash with deionized water, and dry to obtain a sulfonic acid-phosphoric acid zirconium hybrid cation exchange membrane.
[0012] In the cation exchange membrane casting solution, the mass ratio of zirconium oxychloride to polyvinylidene fluoride is (1 - 3):(8 - 10); the concentration of polyvinylidene fluoride is (1 - 2) g / L of the concentration of the sodium polystyrene sulfonate solution.
[0013] As a limitation of the present invention, the preparation method of the iron-loaded catalytic intermediate layer is as follows: Add ferrous sulfate to deionized water, stir evenly to obtain a ferrous sulfate solution, add tetrabutyl titanate to the ferrous sulfate solution, stir evenly, and perform ultrasonic dispersion to obtain a tetrabutyl titanate dispersion. Add hydrochloric acid dopamine to Tris buffer solution, stir evenly to obtain a dopamine hydrochloride solution. By means of spraying, spray the dopamine hydrochloride solution and the tetrabutyl titanate dispersion into a film, and the spraying rate is 400-500 μL / min. After spraying, cure at 40-50 °C for 20-30 min to obtain the iron-loaded catalytic intermediate layer.
[0014] The concentration of the ferrous sulfate solution is (4-6) g / L, the mass fraction of tetrabutyl titanate in the dispersion is 13%-17%, and the concentration of the dopamine hydrochloride solution is (0.8-1.2) g / L.
[0015] As a limitation of the present invention, the preparation method of the quaternized nanocellulose hybrid anion exchange membrane is as follows: Add nanocellulose and deionized water to methanol, perform ultrasonic dispersion for 15-20 min to obtain a nanocellulose dispersion. Add silane coupling agent KH-550 and deionized water to ethanol, stir evenly, then adjust the pH to 4-5 with hydrochloric acid, and then stir at room temperature for 2-4 h. After stirring, add the nanocellulose dispersion, react at 50-70 °C for 2-4 h, cool after the reaction, filter, wash with absolute ethanol and deionized water, and dry at 100-110 °C. Add the dried product and iodomethane to N-methylpyrrolidone, react at room temperature for 18-24 h, centrifuge after the reaction, wash the centrifuged product with ethanol, and freeze-dry to obtain quaternized nanocellulose; Add polyethyleneimine to dimethyl sulfoxide, stir evenly and then add bromoethane, react fully at 50-70 °C for 2-4 h, cool after the reaction to obtain quaternized polyethyleneimine. Add polyvinyl alcohol to dimethyl sulfoxide, stir evenly, then add quaternized polyethyleneimine, KH-560 silane coupling agent and quaternized nanocellulose, perform ultrasonic dispersion for 15-30 min, and then heat and react at 80-90 °C for 2-4 h. Cool after the reaction to obtain a quaternary ammonium salt hybrid anion exchange membrane casting solution. Spin-coat the quaternary ammonium salt hybrid anion exchange membrane casting solution into a film by means of spin coating, and then heat and cure at 60-70 °C for 2-3 h. Cool to room temperature after curing to obtain the quaternized nanocellulose hybrid anion exchange membrane.
[0016] The dosage ratio of nanocellulose to iodomethane is (3-5) g:(20-30) mL, and the mass ratio of polyvinyl alcohol, quaternized polyimide, and quaternized nanocellulose is (20-30):(10-12):(0.2-0.8).
[0017] As a limitation of the present invention, in step 3, during electrodialysis, the dialysis voltage is 10 - 12 V, the dialysis electrode solution is a sodium sulfate solution with a concentration of 0.1 - 0.15 mol / L, the membrane surface flow rate is 10 - 12 cm / s, the temperature of the secondary treatment solution is 25 - 30 °C, and the feeding flow rate is 4 - 6 L / h.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention first mixes carbon dioxide with air, and passes the mixed gas into the fly ash washing solution for decalcification pretreatment of the washing solution, removing calcium ions in the fly ash washing solution. The calcium ions in the washing solution form calcium carbonate precipitation, reducing the alkalinity of the washing solution and adsorbing some heavy metals in the washing solution at the same time, avoiding the influence of calcium ions on the subsequent adsorption and electrodialysis processes.
[0019] The present invention prepares iron-sulfur magnetic mesoporous biochar. During the pyrolysis of straw, pore-forming agents potassium bicarbonate and potassium chloride are added to obtain mesoporous biochar with appropriate pore size, uniform pore distribution, and good specific surface area. Then, magnetic ferrite - magnetite is loaded on the surface and in the pores of the mesoporous biochar by in-situ synthesis, making the mesoporous biochar not only capable of selectively adsorbing heavy metals in the washing solution, but also endowing the biochar with good magnetism, facilitating the separation of the biochar after adsorption. Finally, an iron-sulfur catalyst is loaded on the surface of the magnetic biochar, thereby activating persulfate to have the ability to efficiently oxidize and degrade heavy metal-organic complexes, enabling the release of the complex heavy metals formed during the fly ash washing process, thereby strengthening the removal of heavy metals in the washing solution and reducing the residue of heavy metals in the washing solution.
[0020] The present invention prepares a sulfonic acid group-zirconium phosphate hybrid cation exchange membrane and a quaternized nanocellulose hybrid anion exchange membrane with good chlorine resistance, combines the two ion exchange membranes with a supported iron catalytic intermediate layer, and introduces zirconium phosphate with good acid and oxidation resistance into the polyvinylidene fluoride membrane structure by in-situ synthesis to increase the ion exchange capacity of the membrane, thereby forming a higher membrane potential. At the same time, the reverse migration performance of the membrane is enhanced to block the leakage of chloride ions; sulfonic acid groups with stable properties and negative charges are introduced on the surface of the polyvinylidene fluoride membrane by low-temperature plasma modification, enhancing the attraction of the polyvinylidene fluoride membrane to cations; by using the method of in-situ growth, the iron-based catalyst is fixed in the dopamine intermediate layer. The introduction of the iron-based catalyst provides more active sites for water dissociation, reduces the dissociation resistance of the bipolar membrane water reaction, reduces the transmembrane voltage of the bipolar membrane, and promotes the progress of electrodialysis; quaternized polyimide and quaternized cellulose are added to polyvinyl alcohol and crosslinked and modified with a silane coupling agent. The formed anion exchange membrane surface contains a large number of hydroxyl groups, which can accelerate the transfer of hydroxide ions and has good alkali stability and thermal stability. A bipolar membrane is formed and applied to the electrodialysis process. By applying an external power source, chlorine in the washing solution is promoted to move directionally and concentrated through the ion exchange membrane, so as to achieve the purpose of removing chlorine in the washing solution, making the washing solution meet the sewage discharge standard and be directly discharged or re-enter the production cycle as treated water. Detailed implementation manners
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0022] Fly ash washing solution (liquid-solid ratio is 5 mL / g during washing), straw is purchased from the market, Tris buffer solution (1 mol / L, pH = 8.5), polyvinylidene fluoride (Mw = 400000), polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 99%), polyethyleneimine (Mw = 27000), nanocellulose (diameter: 15 - 25 nm, length: 200 - 300 nm).
[0023] Element content in fly ash washing solution (mg / L)
[0024] Example 1: A method for deeply treating wastewater based on an adsorbent, specifically: Step 1: Mix carbon dioxide and air at a volume ratio of 1:9 to form a mixed gas. Then, introduce the mixed gas into the fly ash washing solution and continuously stir it. Control the flow rate of the mixed gas at 1 mL / min. Meanwhile, monitor the pH of the washing solution at all times. When the pH of the washing solution drops to neutral, stop the ventilation, let it stand for aging, filter, and obtain the decalcified washing solution.
[0025] Step 2: Add the iron-sulfur magnetic mesoporous biochar and sodium persulfate to the decalcified washing solution. The addition amount of the iron-sulfur magnetic mesoporous biochar is 2% of the mass fraction of the decalcified washing solution, and the addition amount of sodium persulfate is 1% of the mass fraction of the decalcified washing solution. Stir at a speed of 200 rpm for 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, filter, and obtain the secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane. Set the dialysis voltage at 12 V, the dialysis electrode solution as 0.1 mol / L sodium sulfate solution, the membrane surface flow rate at 10 cm / s, the temperature of the secondary treatment solution at 25 °C, and the feeding flow rate at 5 L / h to obtain the deeply treated wastewater.
[0026] The preparation method of the iron-sulfur magnetic mesoporous biochar used in Step 2 is as follows: Dry the straw at 80 °C, crush it to remove impurities, and grind it to obtain straw powder with a particle size of 100 μm. Mix 3 g of straw powder, 3 g of potassium bicarbonate, and 10 g of potassium chloride, and ball-mill for 15 min to make them evenly mixed. Then, transfer them to a tubular furnace together. Under nitrogen as the protective gas, heat it up to 900 °C at a heating rate of 5 °C / min and hold for 2 h. After the holding is completed, cool it to room temperature with the furnace sealed. Crush the obtained solid, wash it with deionized water, and dry it at 80 °C to obtain mesoporous biochar; Add 20 g of mesoporous biochar to 800 mL of deionized water. After ultrasonic dispersion for 15 min, add 20 g of ferric chloride and 11.1 g of ferrous sulfate, stir evenly, and add sodium hydroxide to adjust the pH to 10 after complete dissolution to obtain a biochar suspension. Then, react the biochar suspension in a water bath at 80 °C for 1 h. During the reaction, continuously introduce nitrogen into the suspension. After the reaction is completed, separate it by applying an external magnetic field. Wash the separated product with absolute ethanol and deionized water, and dry it at 80 °C to obtain magnetic mesoporous biochar; Add 0.2 g of iron nitrate to 20 mL of deionized water, stir evenly, and dissolve completely to obtain an iron nitrate solution. Subsequently, slowly add 0.38 g of thiourea to the iron nitrate solution, stir evenly, and ultrasonically disperse for 10 min to form a dispersion. Then, evaporate the dispersion to dryness at 80 °C. Mix the solid obtained after evaporation with 10 g of magnetic mesoporous biochar, and then transfer them together to a tubular furnace. Under closed conditions, heat to 900 °C at a heating rate of 5 °C / min and hold for 2 h. After the holding is completed, cool to room temperature with the furnace closed. After the product is crushed, wash it with 0.1 mol / L hydrochloric acid and deionized water, and dry it at 80 °C to obtain iron-sulfur-loaded magnetic mesoporous biochar.
[0027] The preparation method of the bipolar membrane used in Step 3 is as follows: Add 2 g of zirconium oxychloride and 9 g of polyvinylidene fluoride to a mixed solution of 54 mL of N,N-dimethylacetamide and 2 mL of methanol, ultrasonically disperse for 30 min, and then stand for defoaming for 2 h to obtain an exchange membrane casting solution. Use a film coater to spin-coat the exchange membrane casting solution on a metal plate, heat and cure at 60 °C for 3 h, and then cool to room temperature to obtain a zirconium oxychloride hybrid cation exchange membrane; Immerse the zirconium oxychloride hybrid cation exchange membrane in a 10% phosphoric acid solution, heat and react at 110 °C for 2 h. After the reaction is completed, cool to room temperature, wash with hydrochloric acid and deionized water, and dry to obtain a zirconium phosphate hybrid cation exchange membrane; Adjust the pH of the Tris buffer solution to 8 with hydrochloric acid, and add sodium polystyrene sulfonate, stir evenly and dissolve completely to obtain a 1.5 g / L sodium polystyrene sulfonate solution. Under an argon atmosphere, place the zirconium phosphate hybrid exchange membrane in a plasma processor for plasma treatment, control the discharge current to be 4.0 A, and the treatment time to be 10 min. After the treatment is completed, quickly immerse it in the sodium polystyrene sulfonate solution and soak for 2 h. After the soaking is completed, take it out, wash with deionized water, and dry to obtain a sulfonic acid group-zirconium phosphate hybrid cation exchange membrane with a thickness of 0.1 mm; Add ferrous sulfate to deionized water, stir evenly to obtain a ferrous sulfate solution with a concentration of 5 g / L. Add tetrabutyl titanate to the ferrous sulfate solution, stir evenly, and ultrasonically disperse to obtain a dispersion with a mass fraction of tetrabutyl titanate of 15%. Add hydrochloric acid dopamine to the Tris buffer solution, stir evenly to obtain a dopamine hydrochloride solution with a concentration of 1 g / L. Use an ultrasonic spray coater to first spray the dopamine hydrochloride solution on the surface of the sulfonic acid group-zirconium phosphate hybrid cation exchange membrane, and then spray the tetrabutyl titanate dispersion. The volume area ratio of the dopamine solution to the sulfonic acid group-zirconium phosphate hybrid cation exchange membrane is 40 μL / cm 2 , and the volume area ratio of the tetrabutyl titanate dispersion to the sulfonic acid group-zirconium phosphate hybrid cation exchange membrane is 60 μL / cm 2, the spraying rate is 400 μL / min, the surface temperature of the membrane is 40 °C. After spraying, it is continuously cured at 40 °C for 20 min to form a supported iron catalytic intermediate layer with a thickness of 50 nm on the surface of the sulfonic acid group-zirconium phosphate hybrid cation exchange membrane; Add 4 g of nanocellulose and 50 mL of deionized water to 200 mL of methanol, and ultrasonically disperse for 15 min to obtain a nanocellulose dispersion. Add 6 g of silane coupling agent KH-550 and 30 mL of deionized water to 570 mL of ethanol, stir evenly, adjust the pH to 4 with hydrochloric acid, then stir at room temperature for 2 h. After stirring, add the nanocellulose dispersion, react at 70 °C for 2 h, cool after the reaction, filter, wash with absolute ethanol and deionized water, and dry at 110 °C. Add the dried product and 24 mL of iodomethane to 50 mL of N-methylpyrrolidone, react at room temperature for 24 h, centrifuge after the reaction, wash the centrifuged product with ethanol, and freeze-dry to obtain quaternized nanocellulose; Add 10 g of polyethyleneimine to 40 g of dimethyl sulfoxide, stir evenly, add 3.2 mL of bromoethane, and react fully at 60 °C for 2 h. After the reaction, cool to obtain quaternized polyethyleneimine. Add 25 g of polyvinyl alcohol to 100 g of dimethyl sulfoxide, stir evenly, then add 11 g of quaternized polyethyleneimine, 0.5 g of KH-560 silane coupling agent and 0.5 g of quaternized nanocellulose. After ultrasonically dispersing for 15 min, heat and react at 90 °C for 4 h. After the reaction, cool to obtain a quaternary ammonium salt hybrid anion exchange membrane casting solution. Use a film coater to spin-coat the exchange membrane casting solution on the supported iron catalytic intermediate layer, heat and cure at 60 °C for 3 h, and then cool to room temperature to obtain a bipolar membrane (thickness: 0.1 mm + 50 nm + 0.1 mm).
[0028] Example 2: A method for the advanced treatment of wastewater based on an adsorbent, specifically: Step 1: Mix carbon dioxide and air at a volume ratio of 1:9 to form a mixed gas, then pass the mixed gas into the fly ash washing solution and continuously stir. Control the flow rate of the mixed gas at 1 mL / min, and monitor the pH of the washing solution at all times. When the pH of the washing solution drops to neutral, stop ventilation, let it stand for aging, filter, and obtain a decalcified washing solution.
[0029] Step 2: Add supported iron-sulfur magnetic mesoporous biochar and sodium persulfate to the decalcified washing solution. The addition amount of supported iron-sulfur magnetic mesoporous biochar is 1% of the mass fraction of the decalcified washing solution, and the addition amount of sodium persulfate is 1% of the mass fraction of the decalcified washing solution. Stir at a speed of 200 rpm at room temperature for 120 min. After the reaction, separate the supported iron-sulfur magnetic mesoporous biochar by an external magnetic field, filter, and obtain a secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment liquid using a bipolar membrane. Set the dialysis voltage to 11 V, the dialysis electrode liquid to a 0.1 mol / L sodium sulfate solution, the membrane surface flow rate to 11 cm / s, the temperature of the secondary treatment liquid to 25 °C, and the feeding flow rate to 5 L / h to obtain the deeply treated wastewater.
[0030] The preparation method of the iron-sulfur magnetic mesoporous biochar used in Step 2 is the same as that in Example 1.
[0031] The preparation method of the bipolar membrane used in Step 3 is the same as that in Example 1.
[0032] Example 3: A method for deeply treating wastewater based on an adsorbent, specifically as follows: Step 1: Mix carbon dioxide and air at a volume ratio of 1:9 to form a mixed gas. Subsequently, pass the mixed gas into the fly ash washing liquid and continuously stir. Control the flow rate of the mixed gas to 1 mL / min, and simultaneously monitor the pH of the washing liquid at all times. When the pH of the washing liquid drops to neutral, stop ventilation, let it stand for aging, and filter to obtain the decalcified washing liquid.
[0033] Step 2: Add the iron-sulfur magnetic mesoporous biochar and sodium persulfate to the decalcified washing liquid. The addition amount of the iron-sulfur magnetic mesoporous biochar is 2% of the mass fraction of the decalcified washing liquid, and the addition amount of sodium persulfate is 0.5% of the mass fraction of the decalcified washing liquid. Stir at a speed of 200 rpm for 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, and filter to obtain the secondary treatment liquid; Step 3: Perform electrodialysis treatment on the secondary treatment liquid using a bipolar membrane. Set the dialysis voltage to 10 V, the dialysis electrode liquid to a 0.1 mol / L sodium sulfate solution, the membrane surface flow rate to 12 cm / s, the temperature of the secondary treatment liquid to 25 °C, and the feeding flow rate to 5 L / h to obtain the deeply treated wastewater.
[0034] The preparation method of the iron-sulfur magnetic mesoporous biochar used in Step 2 is the same as that in Example 1.
[0035] The preparation method of the bipolar membrane used in Step 3 is the same as that in Example 1.
[0036] Next, based on Example 1, control experiments are carried out, specifically Comparative Example 1, Comparative Example 2, and Comparative Example 3, as described below: Comparative Example 1: This comparative example relates to a method for deeply treating wastewater based on an adsorbent. The difference from Example 1 is that in Step 2, magnetic mesoporous biochar is used to adsorb heavy metals, specifically: Step 1: Mix carbon dioxide and air at a volume ratio of 1:9 to form a mixed gas. Then, introduce the mixed gas into the fly ash washing solution and continuously stir it. Control the flow rate of the mixed gas at 1 mL / min, and monitor the pH of the washing solution at all times. When the pH of the washing solution drops to neutral, stop ventilation, let it stand for aging, filter, and obtain the decalcified washing solution.
[0037] Step 2: Add magnetic mesoporous biochar and sodium persulfate to the decalcified washing solution. The addition amount of the iron-sulfur loaded magnetic mesoporous biochar is 2% of the mass fraction of the decalcified washing solution, and the addition amount of sodium persulfate is 1% of the mass fraction of the decalcified washing solution. Stir at a speed of 200 rpm for 120 min at room temperature. After the reaction is completed, separate the iron-sulfur loaded magnetic mesoporous biochar by an external magnetic field, filter, and obtain the secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane. Set the dialysis voltage at 12 V, the dialysis electrode solution as a 0.1 mol / L sodium sulfate solution, the membrane surface flow rate at 10 cm / s, the temperature of the secondary treatment solution at 25 °C, and the feeding flow rate at 5 L / h to obtain the deeply treated wastewater.
[0038] The preparation method of the magnetic mesoporous biochar used in Step 2 is as follows: Dry the straw at 80 °C, crush it to remove impurities, and grind it to obtain straw powder with a particle size of 100 μm. Mix 3 g of straw powder, 3 g of potassium bicarbonate, and 10 g of potassium chloride, and ball mill for 15 min to make them evenly mixed. Then, transfer them to a tubular furnace together. Under nitrogen as the protective gas, heat it at a heating rate of 5 °C / min to 900 °C and hold for 2 h. After the holding is completed, cool it to room temperature with the furnace sealed. Crush the obtained solid, wash it with deionized water, and dry it at 80 °C to obtain mesoporous biochar; Add 20 g of mesoporous biochar to 800 mL of deionized water. After ultrasonic dispersion for 15 min, add 20 g of ferric chloride and 11.1 g of ferrous sulfate, stir evenly, and adjust the pH to 10 with sodium hydroxide after complete dissolution to obtain a biochar suspension. Then, react the biochar suspension in a water bath at 80 °C for 1 h. Continuously introduce nitrogen into the suspension during the reaction. After the reaction is completed, separate it with an external magnetic field. Wash the separated product with absolute ethanol and deionized water, and dry it at 80 °C to obtain magnetic mesoporous biochar.
[0039] The preparation method of the bipolar membrane used in Step 3 is the same as that in Example 1.
[0040] Comparative Example 2: This comparative example relates to a method for deeply treating wastewater based on an adsorbent. The difference from Example 1 is that in Step 2, mesoporous biochar is used to adsorb heavy metals. Specifically: Step 1: Mix carbon dioxide and air in a volume ratio of 1:9 to form a mixed gas. Then, introduce the mixed gas into the fly ash washing solution and continuously stir. Control the flow rate of the mixed gas at 1 mL / min, and monitor the pH of the washing solution at all times. When the pH of the washing solution drops to neutral, stop ventilation, let it stand for aging, filter, and obtain the decalcified washing solution.
[0041] Step 2: Add the iron-sulfur magnetic mesoporous biochar and sodium persulfate to the decalcified washing solution. The addition amount of the iron-sulfur magnetic mesoporous biochar is 2% of the mass fraction of the decalcified washing solution, and the addition amount of sodium persulfate is 1% of the mass fraction of the decalcified washing solution. Stir at a speed of 200 rpm for 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, filter, and obtain the secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane. Set the dialysis voltage at 12 V, the dialysis electrode solution as a 0.1 mol / L sodium sulfate solution, the membrane surface flow rate at 10 cm / s, the temperature of the secondary treatment solution at 25 °C, and the feeding flow rate at 5 L / h to obtain the deeply treated wastewater.
[0042] The preparation method of the magnetic mesoporous biochar used in Step 2 is as follows: Dry the straw at 80 °C, crush it to remove impurities, and grind it to obtain straw powder with a particle size of 100 μm. Mix 3 g of straw powder, 3 g of potassium bicarbonate, and 10 g of potassium chloride, and ball-mill for 15 min to make them evenly mixed. Then, transfer them together to a tubular furnace. Under nitrogen as the protective gas, heat up to 900 °C at a heating rate of 5 °C / min and hold for 2 h. After the holding is completed, cool it to room temperature with the furnace sealed. Crush the obtained solid, wash it with deionized water, and dry it at 80 °C to obtain the mesoporous biochar.
[0043] The preparation method of the bipolar membrane used in Step 3 is the same as the preparation method in Example 1.
[0044] Comparative Example 3: This comparative example relates to a method for deeply treating wastewater based on an adsorbent. The difference from Example 1 is that in Step 3, in the bipolar membrane used, the cation exchange membrane is a polyvinylidene fluoride membrane. Specifically: Step 1: Mix carbon dioxide and air in a volume ratio of 1:9 to form a mixed gas. Then, introduce the mixed gas into the fly ash washing solution and continuously stir. Control the flow rate of the mixed gas at 1 mL / min, and monitor the pH of the washing solution at all times. When the pH of the washing solution drops to neutral, stop ventilation, let it stand for aging, filter, and obtain the decalcified washing solution.
[0045] Step 2: Add the iron-sulfur magnetic mesoporous biochar and sodium persulfate to the decalcified and washed solution. The addition amount of the iron-sulfur magnetic mesoporous biochar is 2% of the mass fraction of the decalcified and washed solution, and the addition amount of sodium persulfate is 1% of the mass fraction of the decalcified and washed solution. Stir at a speed of 200 rpm for 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, and filter to obtain the secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane. Set the dialysis voltage to 12 V, the dialysis electrode solution to a 0.1 mol / L sodium sulfate solution, the membrane surface flow rate to 10 cm / s, the temperature of the secondary treatment solution to 25 °C, and the feeding flow rate to 5 L / h to obtain the deeply treated wastewater.
[0046] The preparation method of the iron-sulfur magnetic mesoporous biochar used in Step 2 is the same as that in Example 1.
[0047] The preparation method of the bipolar membrane used in Step 3 is as follows: Add 9 g of polyvinylidene fluoride to 54 mL of N,N-dimethylacetamide, and ultrasonically disperse for 30 min to obtain a polyvinylidene fluoride dispersion. Then, let it stand for degassing for 2 h to obtain a cation exchange membrane casting solution. Use a coating machine to spin-coat the exchange membrane casting solution on a metal plate, heat and cure it at 60 °C for 3 h, and then cool it to room temperature to obtain a 0.1 mm thick polyvinylidene fluoride cation exchange membrane; Add ferrous sulfate to deionized water, stir evenly to obtain a ferrous sulfate solution with a concentration of 5 g / L. Add tetrabutyl titanate to the ferrous sulfate solution, stir evenly, and ultrasonically disperse to obtain a dispersion with a mass fraction of tetrabutyl titanate of 15%. Add hydrochloric acid dopamine to Tris buffer solution, stir evenly to obtain a dopamine hydrochloride solution with a concentration of 1 g / L. Use an ultrasonic spraying machine to first spray the dopamine hydrochloride solution on the surface of the sulfonic acid group-phosphoric acid zirconium hybrid cation exchange membrane, and then spray the tetrabutyl titanate dispersion. The volume area ratio of the dopamine solution to the sulfonic acid group-phosphoric acid zirconium hybrid cation exchange membrane is 40 μL / cm 2 , and the volume area ratio of the tetrabutyl titanate dispersion to the sulfonic acid group-phosphoric acid zirconium hybrid cation exchange membrane is 60 μL / cm 2 , and the spraying rate is 400 μL / min. The membrane surface temperature is 40 °C. After spraying is completed, continue to cure at 40 °C for 20 min to form a 50 nm thick iron-loaded catalytic intermediate layer on the surface of the polyvinylidene fluoride cation exchange membrane; 4 g of nanocellulose and 50 mL of deionized water were added to 200 mL of methanol, and ultrasonic dispersion was carried out for 15 min to obtain a nanocellulose dispersion. 6 g of silane coupling agent KH-550 and 30 mL of deionized water were added to 570 mL of ethanol, and after stirring evenly, the pH was adjusted to 4 with hydrochloric acid, and then stirred at room temperature for 2 h. After the stirring was completed, the nanocellulose dispersion was added, and the reaction was carried out at 70 °C for 2 h. After the reaction was completed, it was cooled, filtered, washed with absolute ethanol and deionized water, and dried at 110 °C. The dried product and 24 mL of iodomethane were added to 50 mL of N-methylpyrrolidone, and the reaction was carried out at room temperature for 24 h. After the reaction was completed, centrifugation was carried out, and the centrifuged product was washed with ethanol and freeze-dried to obtain quaternized nanocellulose; 10 g of polyethyleneimine was added to 40 g of dimethyl sulfoxide, and after stirring evenly, 3.2 mL of bromoethane was added, and the reaction was carried out at 60 °C for 2 h. After the reaction was completed, it was cooled to obtain quaternized polyethyleneimine. 25 g of polyvinyl alcohol was added to 100 g of dimethyl sulfoxide, and after stirring evenly, 11 g of quaternized polyethyleneimine, 0.5 g of KH-560 silane coupling agent and 0.5 g of quaternized nanocellulose were added. After ultrasonic dispersion for 15 min, the reaction was carried out at 90 °C for 4 h. After the reaction was completed, it was cooled to obtain a quaternary ammonium salt hybrid anion exchange membrane casting solution. The exchange membrane casting solution was spin-coated on the iron-catalyzed intermediate layer by a coating machine and cured at 60 °C for 3 h, and then cooled to room temperature to obtain a bipolar membrane (thickness: 0.1 mm + 50 nm + 0.1 mm).
[0048] Detection experiment: The same batch of fly ash washing liquid was treated according to the treatment methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 respectively to obtain pre-drained water after treatment, and the residual chlorine and heavy metal contents in the pre-drained water after treatment were detected.
[0049] Residual chlorine content test: According to "Water Quality - Determination of Free Chlorine and Total Chlorine - N,N-Diethyl-1,4-Phenylenediamine Spectrophotometric Method" (HJ 586-2010), an ultraviolet spectrophotometer was used to test the residual chlorine content. 2.0 mL of concentrated sulfuric acid with a concentration of 98% and 0.2 g of solid EDTA disodium were added to 250 mL of deionized water to prepare a mixed solution. 1.1 g of anhydrous DPD sulfate was added to the mixed solution, and after mixing evenly, it was made up to 1000 mL to obtain DPD solution. 24.0 g of anhydrous disodium hydrogen phosphate and 46.0 g of potassium dihydrogen phosphate were dissolved in deionized water in turn, 0.8 g of solid EDTA disodium was added, and after mixing evenly, deionized water was added to make up to 1000 mL to obtain a phosphate buffer solution; The residual chlorine standard solution with a chlorine mass concentration of 1.0 mg / L was diluted into standard test solutions with chlorine mass concentrations of 0 / 0.02 / 0.04 / 0.08 / 0.12 / 0.16 / 0.2 mg / L respectively. 15.0 mL of phosphate buffer solution, 5.0 mL of DPD solution, 100 mL of standard test solution and 1.0 g of potassium iodide were successively placed into a conical flask. After mixing evenly, the absorbance at different chlorine concentrations was measured. Taking the absorbance as the ordinate and the residual chlorine concentration as the abscissa, a standard curve of residual chlorine concentration - absorbance was plotted. 15.0 mL of phosphate buffer solution, 5.0 mL of DPD solution, 100 mL of pretreated pre-drainage water and 1.0 g of potassium iodide were successively placed into a conical flask, mixed evenly to obtain the test solution. Subsequently, the absorbance of the test solution was measured. In the blank sample, deionized water was used to replace the pretreated pre-drainage water, and other conditions were the same. According to the standard curve of residual chlorine concentration - absorbance, the residual chlorine concentration in the test solution was calculated using the absorbance value.
[0050] Heavy metal content test: According to "Determination of 65 Elements in Water Quality - Inductively Coupled Plasma Mass Spectrometry" (HJ700 - 2014), an inductively coupled plasma mass spectrometer was used to test the heavy metal content. First, the pretreated pre-drainage water was filtered with a 0.45 μm filter membrane. After filtration, an appropriate amount of nitric acid was added to adjust the pH < 2 to obtain a mixed solution. 2.0 mL of nitric acid and 1.0 mL of hydrochloric acid were added to 100 mL of the mixed solution, and then it was placed on a hot plate and evaporated at a temperature not exceeding 85 °C until the mixed solution remained 20 mL. After cooling, it was fixed to 50 mL with deionized water to obtain the test solution, and the test solution was detected with an inductively coupled plasma mass spectrometer to detect the heavy metal content in the test solution.
[0051]
[0052] Conclusion: It can be seen from the test results that after treating the fly ash washing liquid by the method of deep treatment of wastewater based on adsorbent proposed in the present invention, the chlorine and heavy metals in the washing liquid are efficiently removed, and the contents of residual chlorine and heavy metals in the treated washing liquid meet the comprehensive sewage discharge standard. The method of deep treatment of wastewater based on adsorbent proposed in the present invention can efficiently remove chlorine and heavy metals in the fly ash washing liquid, and the treated fly ash washing liquid meets the discharge requirements.
[0053] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, it is intended to include all changes falling within the meaning and scope of the equivalent elements of the claims in the present invention.
Claims
1. A method for deeply treating wastewater based on an adsorbent, characterized in that: Specifically: Step 1: Introduce a mixed gas of carbon dioxide and air into the fly ash washing solution to perform decalcification pretreatment on the fly ash washing solution, and obtain a decalcified washing solution; Step 2: Add the iron-sulfur magnetic mesoporous biochar and persulfate to the decalcified washing solution, and stir at a speed of 150 - 200 rpm for 90 - 120 min at room temperature. After the reaction is completed, separate the iron-sulfur magnetic mesoporous biochar by applying an external magnetic field, and filter to obtain a secondary treatment solution; Step 3: Perform electrodialysis treatment on the secondary treatment solution with a bipolar membrane to obtain a deeply treated wastewater.
2. The method for deeply treating wastewater based on an adsorbent according to claim 1, wherein: In Step 1, the volume ratio of carbon dioxide to air is 1:(5 - 10), and the flow rate of the mixed gas is (1 - 5) mL / min; during the ventilation process, always pay attention to the pH of the washing solution, and stop ventilation after the pH of the washing solution is neutral.
3. The method for deeply treating wastewater based on an adsorbent according to claim 1, characterized in that: The preparation method of the iron-sulfur magnetic mesoporous biochar is as follows: Dry the straw at 80 - 90 °C, crush it to remove impurities, and grind it to obtain straw powder with a particle size of 100 - 150 μm. Mix the straw powder, potassium bicarbonate, and potassium chloride, and ball mill for 15 - 20 min to make them evenly mixed. Under nitrogen as a protective gas, heat it to 850 - 900 °C at a heating rate of 5 °C / min and keep it warm for 2 - 3 h. After the heat preservation is completed, cool it to room temperature in a closed state. Crush the obtained solid, wash it with deionized water, and dry it at 80 - 90 °C to obtain mesoporous biochar; Add the mesoporous biochar to deionized water, ultrasonically disperse it for 15 - 20 min, then add ferric chloride and ferrous sulfate, stir evenly, fully dissolve, adjust the pH to 9 - 10 with sodium hydroxide to obtain a biochar suspension. Subsequently, react the biochar suspension in a water bath at 80 - 90 °C for 0.5 - 1 h. During the reaction process, continuously introduce nitrogen into the suspension. After the reaction is completed, separate it with an external magnetic field. Wash the separated product with absolute ethanol and deionized water, and dry it at 80 - 90 °C to obtain magnetic mesoporous biochar; Add ferric nitrate to deionized water, stir evenly, and slowly add thiourea after fully dissolving. Ultrasonically disperse it for 10 - 15 min to form a dispersion. Subsequently, evaporate the dispersion to dryness at 80 - 90 °C. Mix the solid obtained after evaporation with the magnetic mesoporous biochar, and under a closed condition, heat it to 850 - 900 °C at a heating rate of 5 °C / min and keep it warm for 2 - 3 h. After the heat preservation is completed, cool it to room temperature in a closed state. Crush the product, wash it with 0.1 mol / L hydrochloric acid and deionized water, and dry it at 80 - 90 °C to obtain the iron-sulfur magnetic mesoporous biochar.
4. A method for deeply treating wastewater based on an adsorbent according to claim 3, characterized in that: The mass ratio of the straw powder, potassium bicarbonate, and potassium chloride is (2 - 4):(2 - 4):(8 - 12); the mass ratio of the mesoporous biochar, ferric chloride, and ferrous sulfate is (1 - 3):(1 - 3):(0.5 - 1.5); the mass ratio of the ferric nitrate, thiourea, and magnetic mesoporous biochar is (0.1 - 0.3):(0.35 - 0.45):(8 - 12).
5. A method for deeply treating wastewater based on an adsorbent according to claim 1, characterized in that: In Step 2, the dosage of the iron-sulfur magnetic mesoporous biochar is 1-2% of the mass fraction of the decalcified and water-washed solution; the persulfate is one or a mixture of ammonium persulfate, potassium persulfate, and sodium persulfate, and the dosage is 0.5-1% of the mass fraction of the decalcified and water-washed solution.
6. The method for deeply treating wastewater based on an adsorbent according to claim 1, wherein: The bipolar membrane includes a sulfonic acid group-zirconium phosphate hybrid cation exchange membrane with a thickness of 0.08-0.12 mm, a quaternized nanocellulose hybrid anion exchange membrane with a thickness of 0.08-0.12 mm, and a supported iron catalytic intermediate layer in the middle of the two, with a thickness of 30-50 nm.
7. A method for deeply treating wastewater based on an adsorbent according to claim 6, characterized in that: The preparation method of the zirconium phosphate hybrid cation exchange membrane is as follows: Zirconium oxychloride and polyvinylidene fluoride are added to a mixed solution of N,N-dimethylacetamide and methanol, and ultrasonic dispersion is carried out for 20-30 min. Subsequently, standing defoaming is carried out for 1-2 h to obtain a cation exchange membrane casting solution. The cation exchange membrane casting solution is spin-coated into a film, and then heated and cured at 60-70 °C for 2-3 h. After the curing is completed, it is cooled to room temperature to obtain a zirconium oxychloride hybrid cation exchange membrane; The zirconium oxychloride hybrid cation exchange membrane is immersed in a phosphoric acid solution, and heated and reacted at 110-120 °C for 1-2 h. After the reaction is completed, it is cooled to room temperature, washed with hydrochloric acid and deionized water, and dried to obtain a zirconium phosphate hybrid cation exchange membrane; The pH of the Tris buffer solution is adjusted to 7-8 with hydrochloric acid, and sodium polystyrene sulfonate is added and stirred evenly until fully dissolved to obtain a sodium polystyrene sulfonate solution. Under an argon atmosphere, the zirconium phosphate hybrid exchange membrane is treated with plasma, controlling the plasma discharge current to be 4.0-5.0 A and the treatment time to be 5-10 min. After the treatment is completed, it is quickly immersed in the sodium polystyrene sulfonate solution and soaked for 1.5-2 h. After the soaking is completed, it is taken out, washed with deionized water, and dried to obtain a sulfonic acid group-zirconium phosphate hybrid cation exchange membrane.
8. A method for deeply treating wastewater based on an adsorbent according to claim 6, characterized in that: The preparation method of the supported iron catalytic intermediate layer is as follows: Ferrous sulfate is added to deionized water and stirred evenly to obtain a ferrous sulfate solution. Tetrabutyl titanate is added to the ferrous sulfate solution and stirred evenly, followed by ultrasonic dispersion to obtain a tetrabutyl titanate dispersion. Hydrochloric acid dopamine is added to the Tris buffer solution and stirred evenly to obtain a dopamine hydrochloride solution. By means of spraying, the dopamine hydrochloride solution and the tetrabutyl titanate dispersion are sprayed into a film, and the spraying rates are both 400-500 μL / min. After the spraying is completed, it is cured at 40-50 °C for 20-30 min to obtain a supported iron catalytic intermediate layer.
9. The method for deeply treating wastewater based on an adsorbent according to claim 6, characterized in that: The preparation method of the quaternized nanocellulose hybrid anion exchange membrane is as follows: Add nanocellulose and deionized water to methanol, and ultrasonically disperse for 15 - 20 min to obtain a nanocellulose dispersion. Add silane coupling agent KH-550 and deionized water to ethanol, stir evenly, then adjust the pH to 4 - 5 with hydrochloric acid, and then stir at room temperature for 2 - 4 h. After stirring is completed, add the nanocellulose dispersion, react at 50 - 70 °C for 2 - 4 h, cool after the reaction is completed, filter, wash with absolute ethanol and deionized water, and dry at 100 - 110 °C. Add the dried product and iodomethane to N-methylpyrrolidone, react at room temperature for 18 - 24 h, centrifuge after the reaction is completed, wash the centrifuged product with ethanol, and freeze-dry to obtain quaternized nanocellulose; Add polyethyleneimine to dimethyl sulfoxide, stir evenly, then add bromoethane, and react fully at 50 - 70 °C for 2 - 4 h. After the reaction is completed, cool to obtain quaternized polyethyleneimine. Add polyvinyl alcohol to dimethyl sulfoxide, stir evenly, then add quaternized polyethyleneimine, KH-560 silane coupling agent and quaternized nanocellulose, ultrasonically disperse for 15 - 30 min, and then heat and react at 80 - 90 °C for 2 - 4 h. After the reaction is completed, cool to obtain a quaternary ammonium salt hybrid anion exchange membrane casting solution. Spin-coat the quaternary ammonium salt hybrid anion exchange membrane casting solution to form a film, and then heat and cure at 60 - 70 °C for 2 - 3 h. After curing is completed, cool to room temperature to obtain a quaternized nanocellulose hybrid anion exchange membrane.
10. A method for deep treatment of wastewater based on an adsorbent according to claim 1, characterized in that: In step 3, during electrodialysis, the dialysis voltage is 10 - 12 V, the dialysis electrode solution is a sodium sulfate solution with a concentration of 0.1 - 0.15 mol / L, the membrane surface flow rate is 10 - 12 cm / s, the temperature of the secondary treatment solution is 25 - 30 °C, and the feeding flow rate is 4 - 6 L / h.
Citation Information
Patent Citations
Method for recovering calcium salt by treating high Cl high CO2 burning flue gas and waste burning fly ash water washing lotion
CN104128080A
Melting separation treatment method for heavy metal in waste incineration fly ash
CN118109691A
Process for regenerating spent seed materials used in magnetohydrodynamic power generation
US4390402A
Cited By
Deep treatment method based on heavy metal wastewater
CN120887614A
Bipolar membrane electrodialysis method for preparing acid-base from concentrated seawater
CN121494262A